Lifestyle, design process and the creative practice of do-it-yourself (DIY) as a transformative experience - Smith, Nicola Dawn (Curtin University, 2014)
This is the first research project to simultaneously examine gaps evident between professional design process and amateur creative practice (in modifying home), between idealised and realised concepts of self-place, and consumptive and transformative behaviour. The thesis significantly demonstrates the validity of bricolage and hybridity to both design research and practice, providing new models for co-creation and co-design relevant to all those involved in the modification of home and home life; the space of lifestyle.